Pengaruh Digital Marketing dan Kualitas Pelayanan terhadap Keputusan Menabung pada PT Bank Negara Indonesia (Persero) Tbk Kantor Cabang Utama Mayestik - Sanyoto, Bagus; Sudarwanto, Sudarwanto (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
This research was conducted to find out how much influence the promotion and service quality on customer decision savings to the BNI savings product at PT. Bank Nasional Indonesia. In this research using data and information retrieval methods carried out by giving questionnaires to customers of the Mayestik branch of the BNI savings account with a sample of 75 customers. The sampling technique uses random sampling. Each respondent answers 28 questions using a Likert scale. The research method used in this research is quantitative associative where in this study there are 3 variables which are represented by the independent variable namely digotal marketing (X1), Service Quality (X2) and the dependent variable namely Customer Decision Savings (Y). From the results of the t-test the company image has a positive and significant effect on customer loyalty of 3.033 with a significant value of 0,003, while the service quality also has a positive or direct and significant effect on customer decision of 3.965 with a significant value of 0.000. From the results of testing the F test, the promotion and service quality together have a positive and significant effect on customer decision of 11.197 with a significant level of 0.000